Contestation of Legal and Social Norms in Early Marriage - Sopiyani, Sopiyani; Maksun, Maksun; Maskur, Ali (Journal of Public Representative and Society Provision, 2025)
This research discusses the phenomenon of early marriage that occurs in Pinayungan Village, Karawang Regency, by highlighting the imbalance between legal norms and social norms prevailing in the community. Although legal regulations, such as Law No. 16 of 2019 and PERMA No. 5 of 2019, have regulated the minimum age of marriage and marriage dispensation procedures for the protection of children's rights, the practice of early marriage is still rampant. Through a juridical-sociological approach and qualitative method, this study explores the sociocultural factors behind early marriage, including the belief in the "itung-itungan" tradition and parents' concerns about promiscuity. Interviews with the Religious Affairs Office and one of the children who married early show that social norms in the community take precedence over formal state legal norms. This phenomenon reinforces the concept of "living law" proposed by Eugen Ehrlich. In addition to violating positive law, the practice of early marriage also causes violations of various children's rights guaranteed by the Child Protection Law and the Convention on the Rights of the Child, such as the right to education, health, decent work, and the right to grow and develop optimally. This study recommends the need for a culture-based legal approach to encourage the effective implementation of child protection and prevention of early marriage.